1974
DOI: 10.3758/bf03197491
|View full text |Cite
|
Sign up to set email alerts
|

Memory for words recently classified

Abstract: Thi: paper describe s research whose goal is to determine the implications 01' verbal classificatory judgrnents for recognition rneruorv and recall. TOII'ard this end, Ss were required to answer 100 queries 01' attribution and superordlnaticn Ils a TW[NGI:: sudden? Is SP1~ACH ecstatic? Is a CORKSCREW an opener Is a DCNGEO;-'; 1 scholar") befare being tested unexpectedly on their ability to rernernber either the uppercase "keywords" or the lowercase "descriptors." l.exical mernorv did not depend on whether a wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
126
3

Year Published

1978
1978
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(159 citation statements)
references
References 17 publications
30
126
3
Order By: Relevance
“…Specifically, Baker and Santa reported that recognition of incongruous items in old contexts was superior to recognition of congruous items in old contexts (.79 vs..70). This finding is at odds with data reported by others (e.g., Arnold, Bower, & Bobrow, 1972;Craik & Tulving, 1975;Schulman, 1974). While recognizing the inconsistencies in usage of the term incongruous, the present experiments employed the term incongruous as it was used in the Baker and Santa (1977) study.…”
Section: Methodscontrasting
confidence: 69%
See 1 more Smart Citation
“…Specifically, Baker and Santa reported that recognition of incongruous items in old contexts was superior to recognition of congruous items in old contexts (.79 vs..70). This finding is at odds with data reported by others (e.g., Arnold, Bower, & Bobrow, 1972;Craik & Tulving, 1975;Schulman, 1974). While recognizing the inconsistencies in usage of the term incongruous, the present experiments employed the term incongruous as it was used in the Baker and Santa (1977) study.…”
Section: Methodscontrasting
confidence: 69%
“…It should be noted, however, that Baker and Santa's incongruous condition is unlike the incongruous conditions of other recent experiments. For instance, compare Baker and Santa's incongruous sentence, "The TRUCK was parked on top of the high school" to Schulman's (1974) queries (e.g., Is VELVET brave? "), or to Craik and Tulving's (1975) sentences (e.g., "The boy met a on the street: SPEECH").…”
Section: Methodsmentioning
confidence: 99%
“…For example, Craik and Tulving (1975) noted that in the classification tasks they used, words that were responded to positively (i.e., category members) were generally better recalled and recognized than were words responded to negatively. Indeed, they introduced the notion of elaboration in order to explain this result, arguing that positive instances could be encoded in an integrated fashion with the encoding question because they were "congruous" with it (Schulman, 1974), whereas negative Johnson-Laird et al's (1978) Experiment 2, employing component-search instructions in addition to the targetsearch instructions they had used. Clearly, for the target-search condition, the same results obtained by Johnson-Laird et al would be predicted on the basis of either an "amount-of-processing" or a "number of retrieval cues" hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The questions referred to either one or two attributes of each word, and the answer could be either yes or no. Both of these manipulations have previously been found to encourage broader or more elaborate encoding (Craik & Tulving, 1975;Klein & Saltz, 1976;Shulman, 1974). While answering the questions about the words, subjects were also required to respond to either a visual or an auditory signal, and reaction time to the signal was taken as the measure of cognitive effort.…”
Section: Empirical Studies Of Cognitive Effort and Memorymentioning
confidence: 99%